THE EFFECT OF COMORBID CONDITIONS ON MORTALITY IN PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION (Journal of Medical & Health Sciences Review, 2025)
Background: Percutaneous coronary intervention (PCI) has comorbid conditions that significantly impact clinical outcomes in such patients. The correlation between comorbidities and mortality is critical in understanding how best to manage patients and enhance the chances of survival among high-risk cardiac patients.Objective: To establish the effects of comorbid states on in-hospital and short-term mortality in patients receiving PCI at the Department of Cardiology, Ch Pervaiz Elahi Institute of Cardiology, Multan.Methods: This study was conducted as a cross-sectional study at Department of Cardiology, Ch Pervaiz Elahi Institute of Cardiology, Multan in the period from March 2025 to August 2025 and involved 420 patients who underwent PCI. Data on demographic, comorbidity, and mortality outcomes was obtained using hospital records. The chi-square tests and logistic regression were used to conduct the statistical analyses with the assistance of SPSS 28.0 to identify the independent predictors of mortality.Results: The in-hospital mortality was 6.9%, and the 30-day postoperative mortality was 8.3%. The most effective predictors of mortality were chronic kidney disease (CKD) and heart failure (OR: 2.83 and 2.41, respectively; p